Behavioural responses of cane toad (Rhinella marina) adults and tadpoles to chemical cues (Bangladesh Journal of Zoology, 2018)
Pheromonal communication may be possible to control the invader animal. Pheromone-induced behavioural changes could be exploited to control invasive species such as the cane toad (Rhinella marina). Injured cane toad tadpoles are known to produce species-specific chemical cues that alert conspecific tadpoles to danger. These chemical cues reduce both the survival rate of other tadpoles and body size at metamorphosis, and suggest that cane toad tadpoles express chemical substances that control the behaviour of other tadpoles. Identification of the chemical substance(s) involving in tadpole could lead to the development of methods to control the behaviour of cane toad. Here, the behaviour of cane toad adults and tadpoles was characterized following exposure to chemical substances extracted from dead cane toad tadpoles using methanol (MeOH) or distilled water (H2O). Adult toads showed signs of avoiding water to which the H2O-extracted chemical cue had been added. By contrast, no differences were observed in the swimming behaviour of tadpoles (control, MeOHor H2O-extracted samples). These data indicate that development of a chemicalbased behaviour control method will require more detailed chemical analyses. We used dead tadpoles to extract chemical substrate, but in future studies, the potential behaviour-controlling chemical cues should be extracted from live cane toad tadpoles.Bangladesh J. Zool. 45(2): 149-157, 2017